Maverick kiosk book drops - Zahari, Muhamad Hazrin; Mohd Nasir, Ammar Izzat; Md Sarani, Nur Liyana Izzati; Jikri, Muhammad Fitri; Abu, Roziya (Universiti Teknologi MARA, Kedah, 2018)
Maverick Kiosk Book Drop is a modified dropbox with online connection and book borrowing and returning features. It is designed to enable peers/students to be able to connect/communicate with each other and at the same time improve their English communication skills. This is because we will be implementing auto translation feature inside this dropbox. Maverick Kiosk Book Drop is suitable to be used in a school resource center and it also have an application software called MVKDP apps which allows the user to register as a member and get access to the voice and chat channels that connect every users from every school resource center that have Maverick Kiosk Book Drop Installed. The user can also search for additional information and reviews about the book that they wish to borrow. The uniqueness of this modified Dropbox will be able to attract young kids and teenager to spend more time in their school resource center and at the same time makes it a lot more convenient for them to borrow or return a book. Novelty and uniqueness: It can connect peers and peers to communicate and help each other. In addition, it also speeds up the process of returning and borrowing book to the library/school resource center.